Effect of nutrition on copper and zinc concentrations in human milk - Mane, Sharmila M.; Patil, Neelam J.; Patharkar, Sachin A.; Bangar, Megha G. (International Journal of Research in Medical Sciences, 2018)
Background: The gross composition of human milk is remarkably constant among women of varying nutritional status. Reliable information is now available on the content, and the principal factor affecting it, of most of the trace elements on human milk. However, for some of the trace elements, there is still a wide variation in reported values in the literature, which is due at least in part, to analytical difficulties. Hence this study was taken up to find out if maternal nutritional status influences the copper and zinc concentrations in colostrum of mother. Methods: Total of 100 mothers were enrolled in the study after obtaining prior informed consent. They were divided into 2 groups - group I had 50 malnourished mothers and group II had 50 well-nourished mothers. Sample digestion was attempted with different quantities of various acids. Analysis of digested colostrum was carried out for copper and zinc. Results: The mean levels of copper and zinc were slightly more among well-nourished than malnourished women. Values of copper were significantly higher in the colostrum of well-nourished as compared to that of the malnourished mothers. Conclusions: The parameters of weight, height weight/height ratio and hemoglobin varied significantly between the well-nourished and malnourished mothers. The difference in milk content of malnourished and well-nourished mothers is not significant for zinc. However, copper levels were significantly higher in well-nourished mothers.